The Decline and Rise of Democracy : A Global History from Antiquity to Today - Stasavage, David (Book collections on Project MUSE., 2020)
Many historical accounts of democracy's rise tend to focus on ancient Greece and pre-Renaissance Europe. Democracy has been an experiment that has unfolded over time and across the world-and its transformation is ongoing. This book draws from global evidence to show that the story is much richer-democratic practices were present in many places, at many other times, from the Americas before European conquest, to ancient Mesopotamia, to precolonial Africa.